Structural and Optical Studies of Ho\(^3+\)/yb\(^3+\) Co-Doped TiO\(^2\) Nanoparticles in Silica Glass - Rai, S. (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2016)
The TiO\(_2\) nanoparticles doped with Ho\(^3+\) and Yb\(^3+\) ions were synthesized by sol gel method. The structure of the samples were characterized by XRD, TEM and by thermo gravimetric analysis. The average particle size of the TiO\(_2\) range from 7-10 nm (in diameter). The result obtained from TEM, XRD studies indicate that the rare earth ions were positioned in low phonon glass. The photoluminescence (PL) and upconversion (UC) properties of Ho\(^3+\) in various concentrations of TiO\(_2\) nanoparticles have been investigated. The PL and UC luminescence depends on particle size and crystal structure and we also observed that the emission of Ho\(^3+\) in silica xerogel was significantly depends on the amount of TiO\(_2\) nanoparticles.